Autism intervention every day! : embedding activities in daily routines for young children and their families - Crawford, Merle J.; Weber, Barbara, 1956- (Baltimore, Maryland : Paul H. Brookes Publishing Co., 2016)
"Children with autism often don't get a diagnosis in their first few years of life--but if a very young child is exhibiting red flags, what should professionals and parents do in the meantime? This book has accessible, real-world solutions for use with children birth to three, with or without an autism diagnosis. A follow-up to the bestselling Early Intervention Every Day!, this practical guide is packed with simple, highly effective suggestions for strengthening critical skills during daily routines, from dressing in the morning to getting ready for bed. Early interventionists and other professionals will learn how to coach families in weaving these activities into everyday life with their child, so that intervention continues long after the professional goes home. DISCOVER HOW TO: Recognize red flags for autism spectrum disorder ; Help children build a foundation for learning to interact, communicate, and participate in routines ; Strengthen skills that are especially challenging for children with autism, such as regulation, flexibility, and social communication ; Support families on the journey from pursuing a diagnosis to accessing services ; Implement concepts and teaching strategies based on applied behavior analysis (ABA) ; Address common challenges that occur during daily routines and activities ; Monitor progress to ensure that the strategies are helping children reach their IFSP goals ; Promote children's participation across settings: in homes, preschools, and other community settings -- PRACTICAL MATERIALS: A downloadable Reinforcer Survey that helps determine specific ways to motivate a young child, tables that assist with problem-solving in order to identify possible reasons for challenging behaviors, and vignettes and case stories that illustrate effective intervention techniques"--
"Equips early intervention providers with strategies for supporting families to facilitate critical skills for young children with autism or with characteristics of autism during typical everyday routines and activities. Focuses on those skills particularly challenging for this population, e.g., regulation, flexibility, social communication"--
Machine generated contents note: About the Authors -- Foreword -- Acknowledgments -- Introduction -- 1. Autism and Early Intervention -- 2. Supporting Parents from Suspicions to Diagnosis to Services -- 3. Principles of Behavior and Teaching Strategies -- 4. Model for Addressing the Core Deficits of Autism -- 5. Building Skills to Support Regulation -- 6. Building Skills to Support Making Sense of Self, Others, and the Environment -- 7. Building Skills to Support Flexibility -- 8. Building Skills to Support Social Communication -- 9. Daily Routines and Common Challenges -- References -- Index.
Includes bibliographical references (pages 113-121) and index.
Keywords: Children with autism spectrum disorders -- Life skills guides; Children with autism spectrum disorders -- Family relationships; Interpersonal relations -- Juvenile literature